Comparison of foam swabs and toothbrushes as oral hygiene interventions in mechanically ventilated patients: a randomised split mouth study. Issue 1 (14th October 2016) - Marino, Paola J; Hannigan, Ailish; Haywood, Sean; Cole, Jade M; Palmer, Nicki; Emanuel, Charlotte; Kinsella, Tracey; Lewis, Michael A O; Wise, Matt P; Williams, David W
Abstract : Introduction: During critical illness, dental plaque may serve as a reservoir of respiratory pathogens. This study compared the effectiveness of toothbrushing with a small-headed toothbrush or a foam-headed swab in mechanically ventilated patients. Methods: This was a randomised, assessor-blinded, split-mouth trial, performed at a single critical care unit. Adult, orally intubated patients with >20 teeth, where >24 hours of mechanical ventilation was expected were included. Teeth were cleaned 12-hourly using a foam swab or toothbrush (each randomly assigned to one side of the mouth). Cleaning efficacy was based on plaque scores, gingival index and microbial plaque counts. Results: High initial plaque (mean=2.1 (SD 0.45)) and gingival (mean=2.0 (SD 0.54)) scores were recorded for 21 patients. A significant reduction compared with initial plaque index occurred using both toothbrushes (mean change=−1.26, 95% CI −1.57 to −0.95; p<0.001) and foam swabs (mean change=−1.28, 95% CI −1.54 to −1.01; p<0.001). There was significant reduction in gingival index over time using toothbrushes (mean change=−0.92; 95% CI −1.19 to −0.64; p<0.001) and foam swabs (mean change=−0.85; 95% CI −1.10 to −0.61; p<0.001). Differences between cleaning methods were not statistically significant (p=0.12 for change in gingival index; p=0.24 for change in plaque index). There was no significant change in bacterial dental plaque counts between toothbrushing (mean change 3.7×10 4 colony-forming units (CFUs); minimum to maximum (−2.5×10 10 CFUs, 8.7×10 7 CFUs)) and foam swabs (mean change 9×10 4 CFUs; minimum to maximum (−3.1×10 10 CFUs, 3.0×10 7 CFUs)). Conclusions: Patients admitted to adult intensive care had poor oral health, which improved after brushing with a toothbrush or foam swab. Both interventions were equally effective at removing plaque and reducing gingival inflammation. Trial registration number: NCT01154257 ; Pre-results.